Swimming As A Risk Factor for Acute Suppurative Otitis Media in A Patient with Contralateral CSOM: A Case Report - Aisyah Nurul Izza Lukman; Andi Tenri Sanna A; Indah hamriani; Samsi Mesi; Hasma Idris Nohong (International Medical Journal Corp. Ltd, 2025)
Background: Acute suppurative otitis media (ASOM) is a short-lived middle ear infection often triggered by Eustachian tube dysfunction. Swimming, especially in unsterile waters, can be a risk factor for ASOM due to the ingress of contaminated water or pressure changes that disrupt middle ear ventilation. Individuals with contralateral chronic suppurative otitis media (CSOM) are at higher risk due to pre-existing anatomical changes and decreased mucociliary defense. Case Report : A 36-year-old man, a physical education teacher, presented with severe pain in his right ear for one week, worsening the previous night, accompanied by otorrhea and hearing loss. The complaints arose after water entered the patient's ear while teaching swimming. Otoscopic examination revealed a 40–50% tympanic membrane perforation with hyperemia in the right ear, and a 20–30% perforation without hyperemia in the left ear. Tuning fork and audiometric examinations confirmed bilateral conductive hearing loss (mild in the right ear, moderate in the left ear). The patient was diagnosed with ASOM dextra and inactive chronic otitis media sinistra, then given therapy with Burow's tampon, oral ciprofloxacin, methylprednisolone, acetylcysteine, and education regarding the possibility of operative measures. Discussion : This case demonstrates a relationship between water exposure during swimming and the development of ASOM in a patient with contralateral CSOM. The underlying mechanisms involve Eustachian tube dysfunction, impaired middle ear ventilation, and bacterial colonization due to decreased mucociliary defense. The CSOM condition on one side can be a predisposing factor for acute infection on the other side through tube dysfunction and cross-colonization. Comprehensive management includes eradication of infection, control of inflammation, improvement of middle ear ventilation, and patient education to prevent complications such as permanent hearing loss. Conclusion : Swimming in unsterile waters can be a gateway for infection causing ASOM, especially in individuals with contralateral CSOM. Early and comprehensive treatment is crucial to prevent complications and preserve hearing function.